Promoting the Principle of Political Equality: Reformulation of Private Funding Source Regulations for Indonesian Political Parties - Mamonto, Moch Andry Wikra Wardhana; Radzi, Mohd Shahril Nizam Bin Md; Moenta, Andi Pangerang; Ilmar, Aminuddin; Riza, Marwati (Universitas Negeri Semarang, 2024)
This study examines the regulation of private funding sources for political parties, with the goal of developing a framework that ensures political equality for donors. Adopting a normative legal research approach, the study employs statutory, conceptual, and comparative methods. Data are analyzed descriptively and prescriptively to offer a comprehensive understanding of the current regulatory gaps and to propose a ius constituendum for the regulation of private political party funding. The findings reveal two key issues. First, while Indonesia has regulations governing private funding for political parties, these regulations do not comprehensively address all private funding sources, leaving certain sources unregulated or insufficiently restricted. Second, the existing regulatory framework fails to ensure political equality among donors. Based on these findings, the study recommends several reforms for more equitable regulation. Specifically, it advocates for a regulatory framework that prioritizes political equality, with detailed classifications of private funding sources—distinguishing between internal sources, such as party taxes from members holding political positions, and external sources, such as loans from individuals or legal entities. Additionally, the study proposes establishing clear limits on donor contributions, including maximum limits for both member contributions and party taxes. These reforms aim to create a more transparent and balanced system of political financing, ensuring fairer access to the political process for all donors.